Pengaruh Konsentrasi Oksidator pada Proses Hidroksilasi Minyak Jarak (Castor Oil) Dengan atau Tanpa Proteksi Gugus Hidroksi - Marlina Marlina; N. M. Surdia; C. L. Radiman; S. Achmad (Institute for Research and Community Services (LPPM) ITB, 2004)
Oil is derived from the bean of castor plant ricinus communis l., belonging to euphorbiaceae family. Oil rendement per gram of castor bean is 45